Effect of Nitrogen Sources on Diatoms Growth and Nutritional Value for Enhancing Litopenaeus vannamei Larval Performance - Reham A. Abdelhay; Mohammad S. El-Mor; Mohammed A. M. Salem; Adham A. Al-Sagheer; Yasmina M. Abd-Elhakim; Bayan A. Hassan; Hossam A. M. Mounes (Animals)
This study investigated the impact of different nitrogen sources on the growth and biochemical composition of two diatom species, Chaetoceros calcitrans and Thalassiosira weissflogii, and evaluated their use as live feed for Litopenaeus vannamei larvae. Diatoms were cultured in a Conway medium supplemented with four nitrogen sources: potassium nitrate (control), urea, ammonium sulfate, and ammonium nitrate. In a separate experiment, white-leg shrimp larvae (300 larvae/L) at stage Nauplius 6 were fed diets consisting of C. calcitrans, T. weissflogii, or a combination of both diatoms under controlled conditions. The results indicated that urea, ammonium nitrate, and ammonium sulfate significantly enhanced the growth and nutrient composition of C. calcitrans and T. weissflogii compared to the control (potassium nitrate). In C. calcitrans, ammonium nitrate significantly increased protein and lipid contents, while carbohydrate levels were the highest in the control. Similarly, urea and ammonium sulfate treatments yielded the highest lipid levels, whereas the control exhibited the lowest. For T. weissflogii, the control achieved the highest cell count on day 4, but ammonium nitrate significantly improved protein and lipid contents while reducing carbohydrate levels. A mixed diet of C. calcitrans and T. weissflogii significantly enhanced growth performance and reduced mortality rates in L. vannamei larvae compared to single-species diets. In conclusion, the findings indicated that ammonium nitrate was an efficient nitrogen source for enhancing diatom growth. Additionally, combining C. calcitrans and T. weissflogii as a diet improved growth and survival of L. vannamei larvae, offering practical implications for aquaculture.